Oral contraceptive among risk factors for women with ischemic stroke - Carla S. PALUDO; Amanda SACHETTI; Maiara S. PAIXÃO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To evaluate the frequency of use of oral contraceptives and other risk factors among women with ischemic stroke seen at a hospital in the northern region of the state of Rio Grande do Sul. Methods: Prospective, cross-sectional study. The population was characterized by patients admitted with a diagnosis of ischemic stroke during a period from March to August 2019 and the sample by female patients found in the population. The data were collected through an individual interview using a questionnaire developed by the researchers and tabulated for further analysis. All analyzes were performed using the statistical program Bioestat 5.0, considering p = 0.05. Results: In the characterization of the sample, an average age of 68.2 years was observed. The occurrence of gender was 52.4% for women. The mean hospital stay was 12.2 ± 8.91 days. Outcome of hospital discharge was 89.1%. The mean value of body mass index was 25 ± 4.89 kg / m², with an average of 27.4 kg / m² in patients who used oral contraceptives and 25.23 kg / m² in patients who did not use oral contraceptives. The sample had a 34.5%incidence of oral contraceptive use. The average age of those who used oral contraceptives was 62.4 years and of the patients who did not use it was 70.3 years. Conclusion: The study showed a high use of oral contraceptives in the sample, with percentage values very close to other factors evaluated, thus showing itself as a probable risk factor for the development of ischemic stroke.